1999
DOI: 10.1046/j.1523-1755.1999.07310.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the parathyroid hormone gene by vitamin D, calcium and phosphate

Abstract: Regulation of the parathyroid hormone gene by vitamin D,late the PTH gene and these will be considered in the calcium, and phosphate. Secondary hyperparathyroidism is a present review. frequent complication of chronic renal failure resulting in severe bone disease. Secondary hyperparathyroidism is composed of increased in parathyroid hormone (PTH) synthesis THE PTH GENEand secretion due to an increase in PTH gene expression andThe parathyroid cell is committed to the synthesis of parathyroid cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 27 publications
1
37
0
2
Order By: Relevance
“…Torres et al [18] reported that in dialysis patients not using vitamin D, serum PTH level lower than 120 pg/ml (13.2 pmol/l) was highly predictive of low bone turnover with a positive predictive value of 90%. It is well documented that serum PTH is regulated by serum Ca, P and vitamin D [26][27][28][29][30][31][32][33][34][35]. However, apart from these factors, Mg may play an important role in regulating serum PTH level.…”
Section: Discussionmentioning
confidence: 99%
“…Torres et al [18] reported that in dialysis patients not using vitamin D, serum PTH level lower than 120 pg/ml (13.2 pmol/l) was highly predictive of low bone turnover with a positive predictive value of 90%. It is well documented that serum PTH is regulated by serum Ca, P and vitamin D [26][27][28][29][30][31][32][33][34][35]. However, apart from these factors, Mg may play an important role in regulating serum PTH level.…”
Section: Discussionmentioning
confidence: 99%
“…(8,13). At a lower Ca S for PTH , the production of PTH is not necessarily decreased, although increased free plasma 1,25(OH) 2 D 3 , the abundantly circulating 25(OH)D 3 , and increased plasma Ca 2ϩ levels have been reported to have an inhibiting effect on the production of PTH (50,51). Histological evaluation of the activity of the parathyroid glands at the end of the study did not show any obvious differences between HVitD and CVitD dogs.…”
Section: Discussionmentioning
confidence: 78%
“…The study demonstrated that PTH increased bone matrix formation within cultured femurs. PTH primarily functions to increase blood calcium concentration, 25 but in addition is critically involved in skeletal remodeling processes, via its abilities to couple the osteoblast and osteoclast activity, and signal in osteocytes. 26 PTH has recorded some success in the clinical arena, with the recombinant form of PTH (1-34), Teriparatide, gaining Food and Drug Administration (FDA) approval for the treatment of severe osteoporosis.…”
Section: Discussionmentioning
confidence: 99%